# Use the law of exponents to rewrite the following as a sum or difference and without exponent: A) `log_a (x^2/(yz^3))` B) `log (x/(^3sqrt(1-x)))`

*print*Print*list*Cite

Expert Answers

hala718 | Certified Educator

a)`log_a (x^2/(yz^3)`

First we will expand the logarithm using the properties.

`==> log_a (x^2/(yz^3))= log_a x^2 - log_a y - log_a z^3`

Now we will use the power property.

`==> log_a (x^2/(yz^3)) = 2log_a x -log_a y -3log z`

b) `log (x/(^3sqrt(1-x))) `

`log (x/(^3sqrt(1-x))) = log x - log ^3sqrt(1-x) `

`= log x - log (1-x)^(1/3) `

`= log x - (1/3) log (1-x)`

``